Examination of renewable energy sources and their endowments - Nagy, Orsolya (Acta Agraria Debreceniensis, 2012)
Due to the exhaustion of fossile fuel reserves, the increase of their prices on the world market and the environmental pollution resulting from their use make alternative energy sources increasingly important. In my study, I am going to present the currently known and researched renewable energy sources. Based on the results achieved from the SWOT analysis, I provide an overview on the future opportunities of their use. After the comprehensive examination of alternative energy sources, I give insight into the factors which influence the energetic use and utilisation of biomass, as well as the theoretical background of bioenergy. In my work, I pay particular attention to the analysis of the use of biomass as an energy source, as well as the difficulties related to its utilisation.